Marginal abatement cost analysis of cleaner power production alternatives for sustainable energy transition - Garcia, Júlio Lemos; da Cunha, Guilherme Pereira; de Medeiros, José Luiz; Araújo, Ofélia de Queiroz F. (Frontiers in Materials, 2025)
Energy transition is a global transformation driven by greenhouse gas climate change in which fossil power production is replaced by fully renewable counterparts. Currently, the world has accomplished a small fraction of the energy transition. The main reason is that fossil energy sources are still abundant, cost-effective, portable, and easily implementable, while renewable sources are still technologically incipient, costly, cumbersome, portable, intermittent/seasonal, and land-intensive. Because the world cannot suddenly get rid of fossil power production, the compromise is to convert it into sustainable production by attaching carbon abatement processes (anti-carbon packages). Moreover, it is also conducive to migrating from carbon-intensive fossil power production to less carbon-intensive ones. This trend is perceptible as coal-fired plants are being replaced by natural gas combined cycles characterized by maximum thermodynamic yields and minimum carbon emitted per kWh among all fossil analogs. Thus, a conceivable next step of energy transition is to implement natural gas combined cycles with anti-carbon packages. This work compares three anti-carbon packages—post-combustion, oxy-combustion, and pre-combustion—attached to a typical natural gas combined cycle. A differential is the novel marginal abatement cost (MAC) adopted as an economic-environmental performance metric. It is shown that the post-combustion combined cycle requires the minimum investment (596.89 MMUSD) and attains the maximum net value (2,060.68 MMUSD) and minimum MAC (4.58 USD/tCO2), making it the best economic-environmental compromise. The oxy-combustion combined cycle attains the maximum investment (1,095.19MMUSD) and intermediary MAC (12.09 USD/tCO2) and net value (1,144.21 MMUSD) but offers the best social benefit per environmental harm (PowerExported/CO2Emitted= 51.63 MWh/tCO2). The pre-combustion combined cycle has a minimum net value (339.66 MMUSD) and a maximum MAC (28.17 USD/tCO2) and is likely the worst decarbonized combined cycle according to all metrics.